A Brazilian Bacillus thuringiensis strain highly active to sugarcane borer Diatraea saccharalis (Lepidoptera: Crambidae) - Gitahy, Patrícia de Medeiros (2007)
The control of the major sugarcane pest, Diatraea saccharalis, is limited by the stem location of the caterpillar. As part of a long-term project towards the development of an alternative and efficient delivery system of Cry proteins to control the sugarcane borer, the current work describes the selection and characterization of a Brazilian B. thuringiensis strain with prominent activity towards D. saccharalis. Strain S76 was eleven-fold more active than the HD-1 Lepidoptera-standard strain, as estimated by the LC50 of 13.06 µg/L and 143.88 µg/L, respectively. We observed bipiramidal and cuboidal crystals similar to those found in other B. thuringiensis strains with entomopathogenic activity against Lepidoptera and Diptera. In addition, smaller and spherical crystalline inclusions were also observed. The plasmid profile of strain S76 is similar to that of HD-1. PCR amplifications of S76 DNA using cry specific primers confirmed the presence of cry1Aa,cry1Ab,cry1Ac,cry2Aa1, and cry2Ab2, but not cry1Ad, cry2Ac and cry9 type genes. No differences that could explain the superior activity of S76 when compared to HD-1, the Lepidoptera standard strain, were observed. Nevertheless, its higher entomopathogenic activity has pointed this strain S76 as a potential source of cry genes to control sugarcane borer, an important pest that affects sugarcane, a crop that occupies a planted area of about 6 million ha in Brazil.